Gaya Pencitraan Ilustrasi Pada Kaos Band Indie Di Indonesia - Citra Kemala Putri (Universitas Informatika dan Bisnis Indonesia, 2020)
The birth of Counter Culture and subculture are associated with the development of postmodernism. The various of counter cultures and subcultures then bared new cultural activities and products, one of which was indie music. Like a domino effect, indie music then produces subcultural music consumption activities, thus contributing to the growth of fan culture and shopping activities. Indie band merchandises later became a potential commodity. One of the most consumed form of merchandises is indie band t-shirts with illustration on it.. This study is analized the illustrative imagery style that used on various indie band t-shirts in Indonesia. The aim of this study is to get tendency of ilutrative imagery that used by illutrated t-shirts of bands which come from many genres . This research uses qualitative method which is supported by various data sources. The results of this study reveal that quite visible differences between “loud” or “quiet” music genre could be seen in the colors selection and objects selection in the illustration. Both “loud” or “quiet” indie bands use both illustrative imagery style either literal imagery or metaphor imagery on their t-shirt illustrations to communicate the identity and selling points of each of these bands